DİYANET ÇOCUK YOUTUBE CHANNEL ACCORDİNG TO QURAN COURSE INSTRUCTORS FOR 4-6-YEAR-OLDS - Erten, Ramazan; Karateke, Tuncay (Dicle University, 2024)
YouTube is one of the leading platforms that utilize the Web 2.0 infrastructure. With its rich offerings to users, the platform is used for various purposes. One of the main purposes is the use of YouTube as an educational tool. Many institutions and organizations use YouTube for this purpose, and one of them is the Presidency of Religious Affairs (Diyanet İşleri Başkanlığı). This study aims is to assess the Diyanet Çocuk YouTube channel based on the opinions of Quran course instructors for 4-6-year-olds. We conducted the study employing the qualitative approach in the pattern of case study. Purposive sampling method was used in the research. A sample of 20 Quran course instructors working in Şanlıurfa province was selected. Semi-structured interview form and document analysis technique were used in data collection, and content analysis technique was used in analysis. According to the results obtained in the research, participants found the content on the Diyanet Çocuk YouTube channel suitable for children and used positive expressions both about the content and the channel in general. In addition, it was found that they also expressed the shortcomings and deficiencies of the channel. Various recommendations were made based on the results obtained in the research.

YouTube Web 2.0 altyapısı kullanan platformların başında gelmektedir. Kullanıcılarına sunduğu imkanlar bakımından oldukça zengin olan platform, pek çok farklı amaçla kullanılmaktadır. Bu amaçların başında ise YouTube’un eğitimde bir materyal olarak kullanılması bulunmaktadır. Bu amaçla YouTube’u kullanan pek çok kurum ve kuruluş vardır. YouTube’u eğitim amacıyla kullanan kurumlardan bir tanesi de Diyanet İşleri Başkanlığıdır. Bu çalışmanın amacı 4-6 Yaş Kuran Kursu Öğreticilerinin görüşleri doğrultusunda Diyanet Çocuk Youtube kanalının değerlendirilmesidir. Bu çalışma nitel yaklaşımın durum deseninde gerçekleştirilmiştir. Araştırmada amaçlı örnekleme yöntemi kullanılmıştır. Örneklem olarak Şanlıurfa ilinde görev yapan 20 Kuran kursu öğreticisi seçilmiştir. Araştırma verilerinin toplanmasında yarı yapılandırılmış görüşme formu ve doküman incelemesi tekniği, analizinde ise içerik analizi tekniği kullanılmıştır. Araştırmada ulaşılan sonuçlara göre katılımcılar Diyanet Çocuk YouTube kanalında bulunan içerikleri çocuklara uygun görmüş ve hem içerikler hemde kanal ile ilgili genel olarak olumlu ifadeler kullanmışlardır. Bunun yanında katılımcılar kanalda bulunan içeriklerin çocukları meraklandırmaması gibi ifadeler ile de kanalın olumsuzlukları ve eksikliklerini ifade ettikleri tespit edilmiştir. Araştırmada ulaşılan sonuçlar doğrultusunda bu içeriklerin işitme engelli bireylere uygun olarak yeniden revize edilmesi gerektiği gibi çeşitli önerilerde bulunulmuştur.
4-6 Yaş Kuran Kursu Öğreticilerine Göre Diyanet Çocuk Youtube Kanalı
Keywords: Religious Education; Din Eğitimi; Islamic Studies (Other); İslam Araştırmaları (Diğer)